Students’ Ability in Writing Descriptive Text at Eighth Grade of SMP TD Pardede Foundation Medan - Lilis J. Tamba; Yolani V. Situmorang; Queen H. E. Ginting (STKIP AL HIKMAH SURABAYA, 2020)
This research was aimed to know the eighth grade students of junior high school’s ability in writing descriptive text at SMP TD Pardede Foundation Medan. The design of the research was descriptive quantitative. The object of this research was the score of 23 students in their descriptive text assignment. The method that was used consists of writing assignments, collecting data, and analyzing the data by putting them in certain categories. The students were asked to write a descriptive text about someone or something that they like on a piece of paper with the requirement of three paragraphs in minimum. The technique that was used for analyzing the collected data was divided into four steps: reading the result of the students’ assignment, analyzing the aspects of the descriptive text, determining the score of each student, and making a conclusion based on the result of the data. The data was classified by calculating the average ability, forming categories of scores, and calculating the percentage of each category. The result of this study showed that the majority of students’ ability in writing descriptive text at the eighth grade of SMP TD Pardede Foundation Medan was average. From the total of 23 students that participated in the research, 2 students were classified into poor category, 13 students were classified to average category, and 8 students were classified to good category. The most common mistakes that were faced by students are mechanism and vocabulary .